2008
DOI: 10.1016/j.compscitech.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact and tensile properties of PLA/Cordenka and PLA/flax composites

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
327
2
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 570 publications
(351 citation statements)
references
References 10 publications
19
327
2
3
Order By: Relevance
“…Aspect ratio and particle size proved to influence properties considerably and contrary to many claims published in the literature [15,[33][34][35][36][37][38][39][40][41] we found that interfacial adhesion is rather strong between PLA and lignocellulosic fibers. As a consequence, usually the fracture of the fibers is 4 the dominating micromechanical deformation process, which determines composite strength.…”
Section: Introductioncontrasting
confidence: 54%
“…Aspect ratio and particle size proved to influence properties considerably and contrary to many claims published in the literature [15,[33][34][35][36][37][38][39][40][41] we found that interfacial adhesion is rather strong between PLA and lignocellulosic fibers. As a consequence, usually the fracture of the fibers is 4 the dominating micromechanical deformation process, which determines composite strength.…”
Section: Introductioncontrasting
confidence: 54%
“…This result indicated that the EFB pulp fibers had an effective interaction with the seaweed matrix. As both materials were hydrophilic, they were able to form hydrogen bonds between each other (Bax and Müssig 2008). Subsequently, strong adhesion interaction formed between both components with better wetting of the pulp fiber by the seaweed matrix.…”
Section: Fracture Surface Morphologymentioning
confidence: 91%
“…Only weak bonds are formed between them, such as Van de Waals forces or mechanical anchoring induced by compressive residual stress. Thus, agglomeration of fibers often occurs in the polymer matrix, which eventually deteriorates the strength of the composite (Bax and Müssig 2008;Širvaitiene et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bax and Müssig (Bax and Müssig, 2008;Hughes et al, 2007) used SEM to characterise the failure mechanisms of natural composites. As discussed previously, composites B, C and D showed delamination behaviour without fracture during tensile testing.…”
Section: Effect Of Fibre Configuration On Tensile Propertiesmentioning
confidence: 99%